The U.S.-Mexico border as liminal space: implications for policy and administration. Issue 1 (2nd January 2023) - Elías, María Verónica
ABSTRACT: This paper examines the U.S.-Mexico border by exploring the concepts of otherness and liminality in light of restrictive immigration discourses that otherize undocumented Hispanics as a 'threat to the whole.' Through the use of ethnographic sources this paper argues that face-to-face interactions unveil a much more complex picture of life in the borderlands. The border emerges as a diverse realm of pull and push forces, with most people experiencing resistance and aversion at some point of their lives and opportunity and mobility at others. The liminal – understood as the in-between space along nation-state borders – helps account for the continuously transitional borderland experiences where both possibility and heightened risk may be at stake. Finally, the author suggests ways in which experiential understanding can help foment a more democratic and effective border policy making and implementation process.